Tissue‐Engineered Tracheal Replacement in a Child: A 4‐Year Follow‐Up Study. Issue 10 (2nd June 2015) - Hamilton, N. J.; Kanani, M.; Roebuck, D. J.; Hewitt, R. J.; Cetto, R.; Culme‐Seymour, E. J.; Toll, E.; Bates, A. J.; Comerford, A. P.; McLaren, C. A.; Butler, C. R.; Crowley, C.; et al.
Abstract : In 2010, a tissue‐engineered trachea was transplanted into a 10‐year‐old child using a decellularized deceased donor trachea repopulated with the recipient's respiratory epithelium and mesenchymal stromal cells. We report the child's clinical progress, tracheal epithelialization and costs over the 4 years. A chronology of events was derived from clinical notes and costs determined using reference costs per procedure. Serial tracheoscopy images, lung function tests and anti‐HLA blood samples were compared. Epithelial morphology and T cell, Ki67 and cleaved caspase 3 activity were examined. Computational fluid dynamic simulations determined flow, velocity and airway pressure drops. After the first year following transplantation, the number of interventions fell and the child is currently clinically well and continues in education. Endoscopy demonstrated a complete mucosal lining at 15 months, despite retention of a stent. Histocytology indicates a differentiated respiratory layer and no abnormal immune activity. Computational fluid dynamic analysis demonstrated increased velocity and pressure drops around a distal tracheal narrowing. Cross‐sectional area analysis showed restriction of growth within an area of in‐stent stenosis. This report demonstrates the long‐term viability of a decellularized tissue‐engineered trachea within a child. Further research is needed to develop bioengineered pediatric tracheal replacements with lower morbidity, better biomechanics and lower costs. Abstract : This case presents a 4‐year follow‐up of a tissue‐engineered pediatric tracheal transplant and reports on the longterm viability of this approach and areas for further research.